Intellectual property, innovation and trade: strategies for the actualisation of agenda 2063 of the African Union - Maiga, Philda (Department of Commercial Law, 2025)
This thesis investigates the role of intellectual property, innovation, and trade in achieving the agriculture-related goals of Agenda 2063, a strategic framework for Africa's development. The central research question is: How can intellectual property, innovation, and trade be leveraged to actualise the agriculture-related goals of Agenda 2063, and what legal and policy mixes are necessary to achieve these goals? Employing doctrinal analysis, the research establishes agriculture as a key stimulus for Agenda 2063, given its substantial contribution to the Gross Domestic Product of many African economies. Despite its importance, the sector faces persistent challenges including climate change, limited technological capacity, and low adoption of advanced agricultural technologies—factors that hinder productivity and necessitate urgent reform measures. Recognising intellectual property, innovation, and trade as key enablers of development, the thesis links these elements to the realisation of the agriculture-related goals of Agenda 2063. It explores the legal and policy frameworks essential for transforming the sector, with emphasis on intellectual property laws related to agricultural technologies, particularly patents and plant breeders' rights. Innovation and trade are discussed in relation to their interdependency, acknowledging that intellectual property solutions alone are insufficient to achieve holistic results. Findings show that while intellectual property rights have the potential to facilitate the materialisation of Agenda 2063 goals, many African countries face challenges that undermine their effectiveness in promoting agricultural development. Most intellectual property laws strictly comply with the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and impose rigid standards, often neglecting the flexibilities that could enhance agricultural productivity. The thesis calls for a pro-development, TRIPS-compliant intellectual property framework that deliberately utilises TRIPS flexibilities, plant breeders' rights, and utility models, alongside supportive policy interventions and greater investment in research and development. The thesis provides policymakers and stakeholders practical recommendations for developing a bespoke, pro-development, TRIPS-compliant intellectual property framework to serve as a principal guide for intellectual property strategies that can support advancements in agriculture and other sectors.